Erratum: AGN feedback in the nucleus of M 51 - Querejeta, Miguel; Bigiel, Frank (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics